Authoritarianism in the Halal Product Guarantee Act of Indonesia: A Contribution to An Ongoing Debate - Rohmah, Siti (UI Scholars Hub, 2020)
This study aims to examine the discourse on authoritarianism in the Halal Product Guarantee Act of Indonesia. The issue raised concerns opinions on or accusations of the Halal Product Guarantee Act of Indonesia reflecting authoritarianism and threatening human rights, specifically, religious beliefs. Furthermore, the discourse on authoritarianism in the Halal Product Guarantee Act of Indonesia states efforts to impose a single interpretation of the provisions in Islamic law. In this study, we investigate the validity of these allegations using a statute and conceptual approach. In this research, we determine that the claim of authoritarianism in the Halal Product Guarantee Law of Indonesia is false. In principle, the Halal Product Guarantee Act does not prohibit the circulation of haram products and thus does not violate the rights of nonMuslims. In addition, centralization of the Indonesian Ulema Council’s authority on the interpretation of halal provisions for a product is necessary to realize the principle of legal certainty.